Interfering with reconsolidation by rimonabant results in blockade of heroin-associated memory - Lin, Jiang; Peng, Yilin; Zhang, Jinlong; Cheng, Junzhe; Chen, Qianqian; Wang, Binbin; Liu, Yuhang; Niu, Shuliang; Yan, Jie (Frontiers in Pharmacology, 2024)
Drug-associated pathological memory remains a critical factor contributing to the persistence of substance use disorder. Pharmacological amnestic manipulation to interfere with drug memory reconsolidation has shown promise for the prevention of relapse. In a rat heroin self-administration model, we examined the impact of rimonabant, a selective cannabinoid receptor indirect agonist, on the reconsolidation process of heroin-associated memory. The study showed that immediately administering rimonabant after conditioned stimuli (CS) exposure reduced the cue-and herion+cue-induced heroin-seeking behavior. The inhibitory effects lasted for a minimum of 28 days. The effect of Rimonabant on reduced drug-seeking was not shown when treated without CS exposure or six hours after CS exposure. These results demonstrate a disruptive role of rimonabant on the reconsolidation of heroin-associated memory and the therapeutic potential in relapse control concerning substance use disorder.